Evaluation of polyphosphoric acid-modified binders using multiple stress creep and recovery and linear amplitude sweep tests. Issue 4 (1st October 2016) - Jafari, Mohammad; Babazadeh, Abbas
Abstract : This paper assesses rutting and fatigue behaviours of polyphosphoric acid (PPA)-modified binders using the advanced tests of multiple stress creep and recovery (MSCR) and linear amplitude sweep (LAS). The PG 58-22 binder was selected as the unmodified binder and the PPA contents ranged from 0.5% to 1.5% with 0.5% increment being added to it. The MSCR test was applied at 40°C, 55°C, 70°C and the performance grade (PG) temperatures of the binders to consider a wide range of high temperatures. To further explore the role of high stress level on the creep and recovery behaviour, the stress of 12.8 kPa was selected to be added to the MSCR standard procedure. Moreover, the LAS test was conducted at the intermediate temperature of 25°C to evaluate the fatigue resistance of the PPA binders. MSCR tests indicate that, for all the selected temperatures and stresses, increasing the PPA content causes the non-recoverable compliance ( Jnr ) and the percent recovery (R) values to be improved. Despite the positive effects, modification of the PG 58-22 base binder with the PPA additives does not ensure an acceptable rutting performance at the field temperatures equal to or higher than the PGs, because of the high Jnr values compared to the American Association of State Highway and Transportation Officials (AASHTO) MP 19-10 limits and also the negative R values of the PPA binders at these circumstances. On the other hand, LAS tests indicate better resistances of the PPA binders to fatigue than that of the PG 58-22 unmodified one. As the PPA content increases, the fatigue performance significantly increases.